21 days of mammalian omega-3 fatty acid supplementation improves aspects of neuromuscular function and performance in male athletes compared to olive oil placebo - Lewis, E.; Radonic, P.; Wolever, T.; Wells, G. (Journal of the International Society of Sports Nutrition, 2015)
Omega-3 polyunsaturated fatty acids (N-3) are essential nutrients for human health and integral components of neural tissues. There is evidence that N-3 supplementation may benefit exercise performance, however, no study has investigated the ergogenic potential of N-3 supplementation. Our objective was to determine the effect of short-term N-3 supplementation on neuromuscular-function and physical-performance in well-trained athletes.